Lithium ion battery and electric equipment

By optimizing the structural parameters of the positive electrode sheet, negative electrode sheet and electrolyte in lithium-ion batteries, the problem of low energy conversion efficiency of lithium-ion batteries is solved, and higher energy conversion efficiency and lower internal resistance are achieved, which extends the Battery life and reduce costs.

CN119297415APending Publication Date: 2025-01-10HUAWEI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310841563.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-10
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

During the charging and discharging process, lithium-ion batteries have low energy conversion efficiency due to the consumption of internal and external impedances of the battery and the electrochemical polarization and concentration polarization during the lithium-ion deintercalation process, which leads to low energy conversion efficiency, which in turn loses part of the energy, and requires the use of external heat dissipation system to process. Heat affects battery performance and cost.

Method used

By optimizing the structural parameters of the positive electrode sheet, negative electrode sheet and electrolyte, including the particle size distribution, specific surface area and surface density of the positive electrode active material, the particle size distribution and compaction density of the negative electrode active material, and the ions of the electrolyte solution Conductivity, viscosity and dielectric constant to reduce the internal resistance of the battery and improve energy conversion efficiency.

Benefits of technology

Significantly reduce the internal resistance of lithium-ion batteries, improve energy conversion efficiency, reduce power loss, extend battery life, reduce system costs, reduce heat accumulation, and improve resource utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a lithium ion battery and electric equipment. The lithium ion battery comprises a positive pole piece, a negative pole piece, a diaphragm between the positive pole piece and the negative pole piece, and electrolyte for infiltrating the diaphragm. Wherein the value of the parameter Kc of the positive pole piece meets the condition that Kc is more than or equal to 3.00 and less than or equal to 6.50; or the value of the parameter Ka of the negative pole piece meets the condition that Ka is greater than or equal to 0.50 and less than or equal to 1.50; or the value of the parameter Ke of the electrolyte is more than or equal to 0.285 and less than or equal to 0.400. The lithium ion battery under the conditions has the advantages of low internal resistance and high energy conversion efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a lithium-ion battery and an electrical device. Background Art

[0002] Lithium-ion batteries with lithium iron phosphate as active material have excellent safety, high energy density and low production cost, and have been widely used in energy storage and power batteries. During the charging and discharging process of lithium-ion batteries, the internal ohmic impedance of the battery and the external connection impedance will consume part of the electric energy. At the same time, the electrochemical polarization and concentration polarization accompanying the lithium ion deintercalation process will also lose part of the energy. The energy conversion efficiency (η) of lithium-ion batteries is defined as the ratio of the energy released during the discharge process (battery output energy) to the energy consumed during charging (battery input energy), and its value is often less than 100%. The energy lost by lithium-ion batteries is mainly converted into irreversible heat, that is, it is necessary to overcome the heat generated by the transmission resistance of electrons and ions inside the battery. Under actual operating conditions, it is necessary to use an external heat dissipation system to replace the heat in time to avoid heat accumulation causing the internal temperature to rise, which in turn leads to a sharp decline in battery performance. In addition, the energy conversion efficiency of lithium-ion batteries determines the energy conversion efficiency of the battery system. Improving the energy conversion efficiency of batteries can reduce the system's kilowatt-hour / mileage cost and reduce power loss, which plays a role in energy conservation and emission reduction. Therefore, energy conversion efficiency is an important indicator for measuring lithium-ion batteries, reflecting the battery energy utilization rate and is related to issues such as resources, cost and environment. Summary of the invention

[0003] The present application provides a lithium-ion battery and an electrical device to reduce the internal resistance of the lithium-ion battery and improve the energy conversion efficiency of the lithium-ion battery.

[0004] In a first aspect, the present application provides a lithium-ion battery. The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator between the positive electrode sheet and the negative electrode sheet, and an electrolyte that soaks the separator; wherein the lithium-ion battery satisfies at least one of the following conditions:

[0005] (1) The positive electrode sheet comprises a positive electrode current collector and a positive electrode material layer coated on both sides of the positive electrode current collector. The positive electrode material layer comprises a positive electrode active material. The surface density of the positive electrode material layer is Wc, in g / cm 2 ; The specific surface area of ​​the positive electrode active material is Sc, in m 2 / g; the particle size distribution of the positive electrode active material is Lc, and the particle size distribution Lc of the positive electrode active material is Lc=(D90c-D10c) / D50c; Kc=Lc×Wc / Sc, and the value of Kc satisfies 3.00≤Kc≤6.50;

[0006] D90c / D50c / D10c represent the particle sizes corresponding to the cumulative particle size distribution percentages of the positive electrode active material particles reaching 90% / 50% / 10% respectively;

[0007] (2) The negative electrode sheet includes a negative electrode current collector and a negative electrode material layer coated on both sides of the negative electrode current collector. The negative electrode material layer includes a negative electrode active material. The compaction density of the negative electrode material layer is Pa, in units of g / cm 3 The specific surface area of ​​the negative electrode active material is Sa, in m 2 / g; the particle size distribution of the negative electrode active material is La, and the particle size distribution La of the negative electrode active material is La=(D90a-D10a) / D50a; Ka=La×Pa / Sa, and the value of Ka satisfies 0.50≤Ka≤1.50;

[0008] D90a / D50a / D10a represent the particle sizes corresponding to the cumulative particle size distribution percentages of the negative electrode active material particles reaching 90% / 50% / 10% respectively;

[0009] (3) The ionic conductivity of the electrolyte is σ e , unit S / cm; viscosity is recorded as η e , unit is mPa / s; dielectric constant is ε e , Ke=σ e ×ε e / η e , the value of Ke satisfies 0.285≤Ke≤0.400; wherein, the test temperature of the ionic conductivity and viscosity is room temperature 25±5°C.

[0010] The lithium-ion battery of the present application can effectively reduce the internal resistance of the lithium-ion battery and improve the energy conversion efficiency of the lithium-ion battery by controlling one of the positive electrode sheet, the negative electrode sheet and the electrolyte to meet one of the conditions (1) to (3) of the present application. The performance of the lithium-ion battery under different conditions is analyzed and explained below.

[0011] Among them, for condition (1), the electrochemical impedance of the positive electrode sheet is limited by the inter-particle and intra-particle ion transport of the positive electrode active material, and is associated with the particle size distribution, specific surface area and surface density of the positive electrode active material. The narrower the particle size distribution of the positive electrode active material, the more uniform the ion deintercalation inside the particle / the smaller the transmission impedance. The larger the specific surface area of ​​the positive electrode active material, the more sites in contact with the electrolyte or the conductive agent, which is more conducive to ion deintercalation / charge transfer. The lower the surface density of the positive electrode sheet, the shorter the ion deintercalation transmission path and the smaller the transmission impedance. Through experimental verification, when the relationship between the particle size distribution Lc of the positive electrode active material, the specific surface area Sc and the surface density Wc of the positive electrode sheet satisfies 3.00≤Kc=Lc×Wc / Sc≤6.50, the impedance contributed by the positive electrode sheet will be significantly reduced, so that the energy conversion efficiency of the lithium-ion battery can be significantly improved.

[0012] For condition (2), the electrochemical polarization impedance of the negative electrode plate is mainly reflected in the interface SEI film impedance and the ion transfer impedance inside the particles. The specific surface area of ​​the negative electrode active material is slightly smaller, and the SEI film impedance is relatively small. The particles of the negative electrode active material have a suitable particle size distribution, and the contact area between the particles of the negative electrode active material is large, which can reduce the charge transfer impedance. In addition, the appropriate compaction density can ensure the pore structure of the negative electrode plate, which is conducive to full contact with the electrolyte and small ion diffusion impedance. The lithium-ion battery of the present application can significantly reduce the impedance contributed by the negative electrode plate by making the relationship between the specific surface area Sa, particle size distribution La, and compaction density Pa of the negative electrode active material in the negative electrode plate satisfy 0.50≤Ka=Sa×Pa / La≤1.50, thereby improving the energy conversion efficiency of the lithium-ion battery.

[0013] Regarding condition (3), the ionic conductivity, viscosity and dielectric constant of the electrolyte affect the ion transport kinetics, ion diffusion and solvation-desolvation effect. An electrolyte with high ionic conductivity, low viscosity and high dielectric constant has high ion transport flux and low impedance. Therefore, the lithium ion battery of the present application is designed by making the ionic conductivity σ of the electrolyte e , viscosity η e , dielectric constant ε e The relationship between them satisfies 0.285≥Ke=σ e ×ε e / η e ≥0.400, which can effectively reduce the transmission resistance of lithium-ion batteries and improve the energy conversion efficiency of lithium-ion batteries.

[0014] In an optional implementation, the lithium-ion battery at least satisfies condition (1). In an optional implementation, the lithium-ion battery at least satisfies condition (1) and condition (2). In an optional implementation, the lithium-ion battery satisfies conditions (1) to (3) simultaneously.

[0015] In an optional implementation, the lithium-ion battery only satisfies condition (1), that is, the positive electrode plate includes a positive electrode current collector and a positive electrode material layer coated on both sides of the positive electrode current collector, the positive electrode material layer includes a positive electrode active material, the surface density of the positive electrode material layer is Wc, the specific surface area of ​​the positive electrode active material is Sc, the particle size distribution of the positive electrode active material is Lc, and the particle size distribution Lc of the positive electrode active material is Lc=(D90c-D10c) / D50c; Kc=Lc×Wc / Sc, and the value of Kc satisfies 3.00≤Kc≤6.50.

[0016] In an optional implementation, the lithium-ion battery satisfies condition (2) on the basis of satisfying condition (1). That is, the positive electrode plate includes a positive electrode current collector and a positive electrode material layer coated on both sides of the positive electrode current collector, the positive electrode material layer includes a positive electrode active material, the surface density of the positive electrode material layer is Wc, the specific surface area of ​​the positive electrode active material is Sc, the particle size distribution of the positive electrode active material is Lc, and the particle size distribution Lc of the positive electrode active material is Lc = (D90c-D10c) / D50c; Kc = Lc×Wc / Sc, and the value of Kc satisfies 3.00≤Kc≤6.50; Moreover, the negative electrode plate includes a negative electrode current collector and a negative electrode material layer coated on both sides of the negative electrode current collector, the negative electrode material layer includes a negative electrode active material, the compaction density of the negative electrode material layer is Pa, the specific surface area of ​​the negative electrode active material is Sa, the particle size distribution of the negative electrode active material is La, and the particle size distribution La of the negative electrode active material is La=(D90a-D10a) / D50a; Ka=La×Pa / Sa, and the value of Ka satisfies 0.50≤Ka≤1.50.

[0017] In an optional implementation, the lithium-ion battery satisfies condition (3) on the basis of satisfying condition (1). That is, the positive electrode plate includes a positive electrode current collector and a positive electrode material layer coated on both sides of the positive electrode current collector, the positive electrode material layer includes a positive electrode active material, the surface density of the positive electrode material layer is Wc, the specific surface area of ​​the positive electrode active material is Sc, the particle size distribution of the positive electrode active material is Lc, and the particle size distribution Lc of the positive electrode active material is Lc = (D90c-D10c) / D50c; Kc = Lc×Wc / Sc, and the value of Kc satisfies 3.00≤Kc≤6.50; and the ionic conductivity of the electrolyte is σ e , viscosity is denoted as η e , the dielectric constant is denoted as ε e , Ke=σ e ×ε e / η e, the value of Ke satisfies 0.285≤Ke≤0.400.

[0018] In an optional implementation, the lithium-ion battery satisfies condition (1), condition (2) and condition (3) simultaneously.

[0019] In an optional implementation, the lithium-ion battery only satisfies condition (2), the negative electrode plate includes a negative electrode current collector and a negative electrode material layer coated on both sides of the negative electrode current collector, the negative electrode material layer includes a negative electrode active material, the compaction density of the negative electrode material layer is Pa, the specific surface area of ​​the negative electrode active material is Sa, the particle size distribution of the negative electrode active material is La, and the particle size distribution La of the negative electrode active material is La=(D90a-D10a) / D50a; Ka=La×Pa / Sa, and the value of Ka satisfies 0.50≤Ka≤1.50.

[0020] In an optional implementation, the lithium-ion battery only satisfies condition (3), and the ionic conductivity of the electrolyte is σ e , viscosity is denoted as η e , the dielectric constant is denoted as ε e , Ke=σ e ×ε e / η e , the value of Ke satisfies 0.285≤Ke≤0.400.

[0021] In an optional implementation, the specific surface area Sc of the positive electrode active material is 5 to 20 m 2 / g, preferably 9 to 14 m 2 / g. The specific surface area of ​​the positive electrode active material directly affects the capacity of its active material, and then affects the battery rate and cycle performance. When the specific surface area of ​​the positive electrode active material is larger, it is beneficial to increase the ion insertion and extraction rate, and the corresponding lithium-ion battery has a higher rate characteristic. However, when the specific surface area of ​​the positive electrode active material increases, it is easier to react with the electrolyte, resulting in poor cycle performance and storage performance. Therefore, by limiting the specific surface area of ​​the positive electrode active material to the above range, the lithium-ion battery can obtain better cycle performance and storage performance on the basis of obtaining higher rate performance.

[0022] In an optional implementation, the particle size distribution of the positive electrode active material is Lc 1.0 to 4.0, preferably 1.4 to 3.5. If the particle size distribution of the positive electrode active material is too small, it is not conducive to improving the compaction density of the positive electrode active layer, and if it is too large, it is not conducive to reducing the transmission impedance. Therefore, in this application, the particle size distribution of the positive electrode active material is limited to the above-mentioned particle size distribution of the positive electrode active material. The narrower the particle size distribution, the more uniform the ion deintercalation and insertion inside the particle / the smaller the transmission impedance.

[0023] In an optional implementation, the compaction density of the positive electrode material layer is 2.20-2.80 g / cm 3 , surface density is 15-65mg / cm 2 By optimizing the compaction density of the positive electrode material layer, the contact resistance of the positive electrode material layer can be reduced and the ion transfer impedance can be reduced on the basis of obtaining a higher energy density.

[0024] In an optional implementation, the positive electrode active particles include at least one of lithium iron phosphate, surface-coated lithium iron phosphate, or doped and modified lithium iron phosphate.

[0025] In an optional implementation, the specific surface area Sa of the negative electrode active material is 0.5 to 3 m 2 / g, preferably 0.9 to 2.5 m 2 / g. The specific surface area of ​​the negative electrode active material is within this range, and there is a suitable contact area between the negative electrode active material and the electrolyte, so that the lithium-ion battery can form a SEI film on the surface of the negative electrode plate during the first charge and discharge process, so that it will not produce too much irreversible capacity loss and the internal resistance will not be too high.

[0026] In an optional implementation, the particle size distribution of the negative electrode active material is La of 1.0 to 2.0, preferably 1.0 to 1.6. If the particle size distribution of the negative electrode active material is too small, it is not conducive to improving the compaction density of the negative electrode active layer, and if it is too large, it is not conducive to reducing the transmission impedance. Therefore, in this application, the particle size distribution of the negative electrode active material is limited to the above-mentioned particle size distribution of the negative electrode active material. The narrower the particle size distribution, the more uniform the ion deintercalation and extraction inside the particle / the smaller the transmission impedance.

[0027] In an optional implementation, the compaction density of the negative electrode material layer is 1.20 to 1.80 g / cm 3 , surface density is 10-40mg / cm 2 By optimizing the compaction density of the negative electrode material layer, the contact resistance of the negative electrode material layer can be reduced and the ion transfer impedance can be reduced on the basis of obtaining a higher energy density.

[0028] In an optional implementation, the ionic conductivity σ of the electrolyte is e 8.0~14.0*10 -3 S / cm, preferably 9.0 to 12.0*10 -3 S / cm. The viscosity of the electrolyte η e It is 2.0 to 4.0 mPa / s, preferably 2.0 to 3.5 mPa / s.

[0029] In a second aspect, the present application provides an electrical device, which includes the lithium-ion battery of the present application.

[0030] The electrical equipment of this application may include several types such as consumer electronic products, electric tools, electric transportation equipment, energy equipment, etc. Among them, consumer electronic equipment may include, for example, mobile phones, computers, tablet computers, display screens, robotic equipment, etc. Electric transportation equipment includes, but is not limited to, electric cars, electric bicycles, etc. Energy equipment includes, but is not limited to, photovoltaic power station system equipment, wind storage power station equipment, AGC frequency modulation power station equipment, power supply equipment, etc.

[0031] For consumer electronic devices, improving the energy conversion efficiency of lithium-ion batteries can reduce power loss, reduce the heat generated by lithium-ion batteries, and avoid heat accumulation that causes rapid decline in battery performance. For electric transportation equipment, improving the energy conversion efficiency of lithium-ion batteries can reduce power loss and reduce the mileage cost of power battery packs. For energy equipment, improving the energy conversion efficiency of lithium-ion batteries can reduce power loss and reduce the cost per kilowatt-hour of energy storage systems.

[0032] The technical effects that can be achieved in the above-mentioned second aspect can be described with reference to the corresponding effects in the above-mentioned first aspect, and will not be repeated here.

[0033] Among them, the data in the above-mentioned possible implementation methods of the present application, such as specific surface area, particle size distribution, compacted density, surface density, ionic conductivity, viscosity and dielectric constant, etc., when measured, the values ​​within the scope of engineering measurement error should be understood to be within the scope specified in the present application. DETAILED DESCRIPTION

[0034] In order to make the objectives, technical solutions and advantages of the present application clearer, the present application will be described in further detail below.

[0035] The terms used in the following embodiments are only for the purpose of describing specific embodiments and are not intended to be limiting of the present application. As used in the specification and appended claims of the present application, the singular expressions "a", "an", "above", "the" and "this" are intended to also include expressions such as "one or more", unless there is a clear contrary indication in the context.

[0036] For ease of understanding, the technical terms used in this application are explained below.

[0037] Energy conversion efficiency: the ratio of the energy released during battery discharge (battery output energy) to the energy consumed during charging (battery input energy).

[0038] D90 / D50 / D10: The particle size corresponding to when the cumulative particle size distribution percentage in the sample reaches 90% / 50% / 10%.

[0039] Particle size distribution: specifically refers to the particle size distribution span of the sample, calculated by the formula L = (D90-D10) / D50.

[0040] Surface density: The weight of the positive electrode material layer or negative electrode material layer coated on the unit area of ​​the electrode plate. If there is no special indication of the double-sided surface density, the surface density refers to the single-sided surface density, and the unit is g / cm 2 .

[0041] Compacted density: The weight per unit volume of the positive electrode material layer or the negative electrode material layer after the electrode sheet is rolled, in g / cm 3 .

[0042] Specific surface area: the total area per unit mass of positive electrode active material or negative electrode active material, in m 2 / g.

[0043] Ionic conductivity: the ionic conductivity of an electrolyte under the action of an electric field per unit length and unit cross-sectional area, expressed in S / cm.

[0044] Viscosity: The property of a liquid to resist shear deformation when flowing, measured in mPa / s.

[0045] Dielectric constant: When an external electric field is applied to the medium, induced charges will be generated, which will weaken the electric field. The ratio of the original external electric field (in a vacuum) to the final electric field in the medium is the dielectric constant. The stronger the polarity of the solvent, the greater the dielectric constant.

[0046] The lithium-ion battery of the embodiment of the present application comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The positive electrode sheet and the negative electrode sheet are arranged opposite to each other. The separator is arranged between the positive electrode sheet and the negative electrode sheet. The electrolyte is filled between the positive electrode sheet and the negative electrode sheet and infiltrates the separator.

[0047] The positive electrode plate includes a positive electrode current collector and a positive electrode material layer coated on the surfaces of both sides of the positive electrode current collector. The positive electrode current collector may be a metal foil, and illustratively, aluminum foil, gold foil, platinum foil, etc. can all be used as the positive electrode current collector. The positive electrode material layer may include a positive electrode active material, a conductive agent, and a binder. Among them, the positive electrode active material is selected from materials that can reversibly embed and deintercalate lithium ions. In some embodiments, the positive electrode active material includes at least one of lithium iron phosphate, surface-coated lithium iron phosphate, or doped-modified lithium iron phosphate.

[0048] The specific surface area Sc of the positive electrode active material is 5 to 20 m 2 / g, preferably 9 to 14 m 2 For example, the specific surface area Sc of the positive electrode active material may be 5 m 2 / g, 7m 2 / g, 8m 2 / g, 10m 2 / g, 12m2 / g, 14m 2 / g, 16m 2 / g, 18m 2 / g or 20m 2 / g.

[0049] The particle size distribution Lc of the positive electrode active material ranges from 1.0 to 4.0, preferably from 1.4 to 3.5. Wherein, Lc = (D90c-D10c) / D50c. Exemplarily, the particle size distribution Lc of the positive electrode active material may be 1.0, 1.2, 14, 1.6, 2.0, 2.5, 3.0, 3.5, 3.8 or 4.0.

[0050] The compaction density of the positive electrode material layer is 2.20 to 2.80 g / cm 3 , surface density Wc is 0.015-0.065g / cm 2 For example, the compaction density of the positive electrode material layer may be 2.20 g / cm 3 , 2.25g / cm 3 , 2.30g / cm 3 , 2.35g / cm 3 , 2.40g / cm 3 , 2.45g / cm 3 , 2.50g / cm 3 , 2.55g / cm 3 , 2.60g / cm 3 , 2.65g / cm 3 , 2.70g / cm 3 , 2.75g / cm 3 or 2.80g / cm 3 The surface density can be, for example, 15 mg / cm 2 , 20mg / cm 2 , 25mg / cm 2 、30mg / cm 2 、35mg / cm 2 , 40mg / cm 2 , 45mg / cm 2 、50mg / cm 2 、55mg / cm 2 、60mg / cm 2 or 65mg / cm 2 .

[0051] The negative electrode sheet includes a negative electrode current collector and a negative electrode material layer coated on both sides of the negative electrode current collector. The negative electrode current collector may be a metal foil, and for example, aluminum foil, gold foil, platinum foil, etc. may be used as the negative electrode current collector. The negative electrode material layer may include a negative electrode active material, a conductive agent, and a binder. For example, the negative electrode active material may be at least one of graphite, surface-coated graphite, surface chemically modified graphite, or element-doped graphite.

[0052] The specific surface area Sa of the negative electrode active material is 0.5 to 3 m 2 / g, preferably 0.9 to 2.5 m 2 / g. For example, the specific surface area of ​​the negative electrode active material may be 0.5 m 2 / g, 0.9m 2 / g, 1.2m 2 / g, 1.5m 2 / g, 1.7m 2 / g, 1.9m 2 / g, 2.0m 2 / g, 2.3m 2 / g, 2.5m 2 / g, 2.8m 2 / g or 3.0m 2 / g.

[0053] The particle size distribution La of the negative electrode active material is 1.0 to 2.0, preferably 1.0 to 1.6. For example, the particle size distribution La of the negative electrode active material may be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.0.

[0054] The compaction density of the negative electrode material layer is 1.20 to 1.80 g / cm 3 , surface density is 10-40mg / cm 2 For example, the compaction density of the negative electrode material layer may be 1.20 g / cm 3 , 1.5g / cm 3 , 1.30g / cm 3 , 1.35g / cm 3 , 1.40g / cm 3 , 1.45g / cm 3 , 1.50g / cm 3 , 1.55g / cm 3 , 1.60g / cm 3 , 1.65g / cm 3 , 1.70g / cm 3 , 1.75g / cm 3 or 1.80cm 3 The surface density can be, for example, 10 mg / cm2 、15mg / cm 2 , 20mg / cm 2 , 25mg / cm 2 、30mg / cm 2 、35mg / cm 2 or 40mg / cm 2 .

[0055] The diaphragm is used to block the passage of electrons and allow the passage of ions. In a possible embodiment, the diaphragm includes but is not limited to a single layer of polypropylene (PP), a single layer of polyethylene (PE), a double-layer stack formed by a PP film and a PE film, a stack formed by two layers of PP films, a three-layer stack formed by sequentially stacking a PP film, a PE film and a PP film, a diaphragm formed by coating a ceramic or polymer adhesive surface, etc.

[0056] The electrolyte is the transmission medium when lithium ions are transmitted between the positive electrode plate and the negative electrode plate. The electrolyte is filled between the positive electrode plate and the negative electrode plate and infiltrates the diaphragm. In the embodiment of the present application, the electrolyte includes an organic solvent, an electrolyte salt and an additive, wherein the electrolyte salt and the additive are both dissolved in the organic solvent. The embodiment of the present application does not limit the specific composition of the electrolyte, as long as the transmission of lithium ions can be achieved.

[0057] The lithium-ion battery of the present invention satisfies at least one of the following conditions (1) to (3):

[0058] (1) The surface density Wc of the positive electrode material layer, the specific surface area Sc of the positive electrode active material, and the particle size distribution Lc of the positive electrode active material satisfy Kc=Lc×Wc / Sc, wherein the value of Kc satisfies 3.00≤Kc≤6.50. Exemplarily, the value of Kc may be, for example, 3.00, 3.60, 4.00, 4.40, 5.00, 5.60, 6.00, 6.20, 6.40, or 6.50.

[0059] (2) The compaction density Pa of the negative electrode material layer, the specific surface area Sa of the negative electrode active material, and the particle size distribution La of the negative electrode active material satisfy Ka=La×Pa / Sa, and the value of Ka satisfies 0.50≤Ka≤1.50. For example, the value of Ka may be, for example, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4 or 1.5.

[0060] (3) Ionic conductivity σ of the electrolyte e , viscosity η e , dielectric constant ε e The relationship between the three satisfies Ke=σe ×ε e / η e , the value of Ke satisfies 0.285≤Ke≤0.400. Exemplarily, the value of Ke may be, for example, 0.285, 0.300, 0.315, 0.350, 0.375 or 0.400.

[0061] Among them, the positive electrode plate has a greater impact on the internal resistance of the lithium-ion battery. In one embodiment, the lithium-ion battery at least satisfies condition (1). In another embodiment, the lithium-ion battery satisfies at least condition (1) and condition (2) at the same time. In another embodiment, the lithium-ion battery satisfies conditions (1) to (3) at the same time. When the lithium-ion battery satisfies conditions (1) and (2) at the same time, the reduction in its internal resistance is greater than when only condition (1) is satisfied. When the lithium-ion battery satisfies conditions (1) to (3) at the same time, the reduction in its internal resistance is the largest. Therefore, when assembling a lithium-ion battery, the positive electrode plate, negative electrode plate and electrolyte of the lithium-ion battery can be made to satisfy conditions (1) to (3) respectively.

[0062] The performance of the lithium-ion battery of the present application will be explained below in conjunction with specific embodiments.

[0063] Positive electrode active material: lithium iron phosphate.

[0064] Negative electrode active material: graphite material.

[0065] Example 1

[0066] This embodiment is a lithium-ion battery, and the specific manufacturing process of the lithium-ion battery is as follows:

[0067] Step S11, weighing 2% polyvinylidene fluoride (PVDF), 2% conductive agent Super P and 96% positive electrode active material by weight, the positive electrode active material in this embodiment is recorded as C1, adding them into N-methylpyrrolidone (NMP) in sequence, stirring and mixing them evenly, coating the slurry on an aluminum foil current collector, drying, cold pressing, and cutting to obtain a positive electrode sheet;

[0068] Step S12, weighing 1.5% CMC, 2.5% SBR, 1% Super P and 95% negative electrode active material by mass percentage, the negative electrode active material in this embodiment is recorded as A1, adding them into deionized water in sequence, stirring and mixing them evenly, coating the slurry on a copper foil current collector, drying, cold pressing, and cutting to obtain a negative electrode sheet;

[0069] Step S13, the positive electrode plate, negative electrode plate and commercial PE separator prepared above are made into a battery cell, packaged with a polymer, filled with lithium-ion battery electrolyte, and made into a 2.4Ah soft-pack lithium-ion battery after processes such as chemical formation, wherein the preparation method of the electrolyte is: as shown in Table 1 Example 1, ethylene carbonate (EC), propylene carbonate (PC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of EC:PC:EMC of 30:5:65, and then lithium hexafluorophosphate (LiPF6) is added to the resulting mixture to a molar concentration of 1 mol / L, and then a lithium salt additive LiPO2F2 with a mass percentage of 0.1% is added.

[0070] Among them, various performance parameters of the positive electrode active materials are listed in Table 1.

[0071] Example 2-Example 4

[0072] The preparation process is the same as that of Example 1, except that the specific surface area and particle size distribution of the positive electrode active material are different, and the rest is the same as that of Example 1. The specific parameters are listed in Table 1.

[0073] Comparative Example 1-2

[0074] The preparation process is the same as that of Example 1, except that the specific surface area and particle size distribution of the positive electrode active material are different, and the rest is the same as that of Example 1. The specific parameters are listed in Table 1.

[0075] Example 5

[0076] The preparation process is the same as that of Example 1, except that the negative electrode active material is different and the surface density of the positive electrode sheet is different, and the rest is the same as that of Example 1. The specific parameters are listed in Table 1.

[0077] Comparative Examples 3-4

[0078] The preparation process is the same as that of Example 5, except that the surface density of the positive electrode sheet is different, and the rest is the same as that of Example 5. The specific parameters are listed in Table 1.

[0079] The preparation process is the same as that of Example 1, except for the type of positive electrode active material, the specific surface area of ​​the positive electrode active material, the particle size distribution and the difference in the positive electrode active material, and the rest is the same as that of Example 1. The specific parameters are listed in Table 1.

[0080] The energy conversion efficiency of each embodiment was tested respectively, and the test results are listed in Table 1.

[0081] Table 1

[0082]

[0083]

[0084] Among them, graphite used as negative electrode active material can be divided into primary particles and secondary particles. Among them, secondary particles are particles formed by the agglomeration of multiple primary particles. Since the particle size of the primary particles inside the secondary particles is smaller, the ion impedance transmission impedance inside them is smaller. Therefore, when other conditions of the lithium-ion battery are the same, the energy efficiency of the corresponding lithium-ion battery using graphite with a secondary particle structure will be higher. In Table 1, when different types of graphite are compared, the consistency of their structures must also be ensured, that is, the lithium-ion batteries corresponding to the graphite with a secondary particle structure are compared with each other, and the lithium-ion batteries corresponding to the graphite with a primary particle structure are compared with each other.

[0085] It can be seen from the test results of Examples 1-4 in Table 1 that, when the surface density of the positive electrode sheet is the same, by changing the particle size distribution and specific surface area of ​​the positive electrode active material in the positive electrode sheet, the energy conversion efficiency of the obtained lithium ion battery will change. When the value range of Kc is within the range of 3.00-6.50 defined in the present application, the energy conversion efficiency of the obtained lithium ion battery can be maintained at a high level. Compared with Comparative Examples 1 and 2, the energy conversion efficiency of the lithium ion battery in the present application embodiment is greatly improved.

[0086] From the comparative test results of Example 5 and Comparative Examples 3-4 in Table 1, it can be seen that, under the conditions of the same particle size distribution and the same specific surface area of ​​the positive electrode active material, changing the surface density of the positive electrode sheet can change the energy conversion efficiency of the lithium-ion battery. Moreover, as the surface density of the positive electrode sheet increases, the improvement in energy conversion efficiency also increases.

[0087] Examples 6-10

[0088] The preparation process is similar to that of Example 1, except that the positive electrode active material and the negative electrode active material are changed. In Examples 6-10, the parameters of the positive electrode active material are the same, and the compaction density of the negative electrode material layer in the negative electrode sheet is the same. The details are listed in Table 2.

[0089] Comparative Examples 5-6

[0090] The difference between Comparative Examples 5-6 and Examples 6-10 is that the negative electrode active materials are different, as shown in Table 2.

[0091] Embodiment 11

[0092] The positive electrode active material used in Comparative Example 1 was used, and a negative electrode active material different from that in Comparative Example 1 was used. The parameters of the negative electrode active material are listed in Table 2.

[0093] Comparative Examples 7-8

[0094] The difference between Comparative Examples 7-8 and Example 11 is that the negative electrode active materials are different, as shown in Table 2.

[0095] Table 2

[0096]

[0097]

[0098] It can be seen from the test results of Examples 6-10 in Table 2 that, when the compaction density of the negative electrode sheet is the same, by changing the particle size distribution and specific surface area of ​​the negative electrode active material in the negative electrode sheet, the energy conversion efficiency of the obtained lithium ion battery will change. When the value range of Ka is within the range of 0.5-1.5 specified in this application, the energy conversion efficiency of the obtained lithium ion battery can be maintained at a high level. Compared with Comparative Examples 5 and 6, the energy conversion efficiency of the lithium ion battery in the embodiment of the present application is greatly improved.

[0099] From the comparative test results of Example 11 and Comparative Examples 7-8 in Table 2, it can be seen that, under the conditions of the same particle size distribution and the same specific surface area of ​​the negative electrode active material, changing the compaction density of the negative electrode plate can change the energy conversion efficiency of the lithium-ion battery. When the compaction density of the negative electrode plate is too high, resulting in a high Ka value, the energy conversion efficiency of the lithium-ion battery tends to decrease.

[0100] Examples 12-15

[0101] Referring to the preparation process of Example 1, the positive electrode active material is C6, the negative electrode active material is A1, and the composition of the electrolyte is changed. The specific parameters of the electrolyte are listed in Table 3.

[0102] Comparative Example 9

[0103] The difference from Examples 12-15 is that the electrolyte is different. The specific parameters of the electrolyte are listed in Table 3.

[0104] Table 3

[0105]

[0106] From the test results of Examples 11-15 in Table 3, it can be seen that when the Ke value of the electrolyte is changed, the energy conversion efficiency of the lithium-ion battery will fluctuate slightly. Compared with Comparative Example 9, the energy conversion efficiency of Examples 11-15 is improved by about 0.5%.

[0107] The above embodiments are related test data of soft-pack batteries, and the following embodiments and comparative examples are test data of hard-pack batteries.

[0108] Example 16 and Comparative Examples 10-14

[0109] Referring to the preparation process of Example 1, a hard-shell battery is formed using a positive electrode sheet, a negative electrode sheet and an electrolyte. In Example 16 and Comparative Examples 10-14, Sc, Lc and Wc of the positive electrode sheet are different, Sa, La and Pa of the negative electrode sheet are different, and σ e , ε e and η e The specific values ​​are listed in Table 4.

[0110] The energy conversion efficiency and internal resistance of the lithium ion batteries of Example 16 and Comparative Examples 10-14 were tested respectively, and the test results are listed in Table 5. The number of tests for each group of lithium ion batteries is multiple, and the range value of each group of energy conversion efficiency test data is the range of the minimum and maximum values ​​of multiple batteries.

[0111] Table 4

[0112]

[0113]

[0114] Table 5

[0115]

[0116] It can be seen from the test results in Table 5 that the energy conversion efficiency of the lithium-ion battery of the embodiment of the present application can basically reach 94.5% or above, while the energy conversion efficiency of comparative examples 10-13 is relatively low, basically below 94%.

[0117] The test method for the energy conversion efficiency of the lithium-ion battery of the embodiment of the present application and the comparative example comprises the following steps:

[0118] 1) The battery cell is discharged at 0.2C constant current to 2.5V at 25℃ and left to stand for 30min;

[0119] 2) Charge the battery at 0.2C constant current and constant voltage at 25°C to 3.65V / 0.05C, and let it stand for 30 minutes;

[0120] 3) The battery cell is discharged at 0.2C constant current to 2.5V at 25℃ and left to stand for 6h;

[0121] 4) At 25°C, charge the cell at a constant current of 0.5C to 3.65V, let it stand for 1 hour, and record the charging energy as E1;

[0122] 5) At 25°C, discharge the battery cell at a constant current of 0.5C to 2.5V, let it stand for 1 hour, and record the discharge energy as E2.

[0123] Energy efficiency η=E2 / E1.

[0124] Test method for internal resistance of lithium-ion battery:

[0125] 1) Discharge the battery to 2.5V at 0.2C and let it stand for 30 minutes;

[0126] 2) Charge the battery to 3.65V at a constant current of 0.2C, then charge at a constant voltage of 3.65V, cut off the current to 0.05C, and let it stand for 30 minutes;

[0127] 3) The battery cell is discharged at 0.2C for 2.5h to 50% capacity (state of charge, SOC), and then left to stand for 30min;

[0128] 4) The battery cell is discharged at 0.2C for 30 seconds, then discharged at 1C for 5 seconds, with no rest between the two discharge rates, and rested for 30 minutes after discharge;

[0129] The ratio of the voltage difference at the end of each 1C discharge and 0.2C discharge divided by the corresponding current difference is the direct current resistance (DCR) at the SOC. This resistance value is the internal resistance of the lithium-ion battery.

[0130] The test methods for particle size distribution, areal density, compacted density, specific surface area, ionic conductivity, viscosity and dielectric constant are as follows.

[0131] Particle size distribution (D90 / D50 / D10) test method: Use laser particle size analysis to measure the intensity and angle of scattered light, and then calculate the cumulative distribution of particle size. D10 is the diameter value on the horizontal axis corresponding to 10% of the cumulative distribution of the vertical axis; D50 is the diameter value on the horizontal axis corresponding to 50% of the cumulative distribution of the vertical axis; D90 is the diameter value on the horizontal axis corresponding to 90% of the cumulative distribution of the vertical axis.

[0132] Surface density test method: punch the pole piece (the pole piece obtained by disassembling the battery cell needs to be soaked in solvents such as DMC to remove residual electrolyte and dried) into an area of ​​1540.25mm 2 The discs are marked as 1 / 2 / 3 / 4 / 5…n, and the masses are weighed as M1 / M2 / M3 / M4 / M5… / M n , the pole piece surface density = [(M1+M2+M3+M4+M5+…M n ) / nM 集流体 ] / 1540.25mm 2 . M 集流体 =ρ 集流体 *L 集流体 *1540.25mm 2 ρ 集流体 is the current collector density, L 集流体is the thickness of the current collector.

[0133] Calculation method of compaction density: compaction density = surface density / (thickness of the electrode after rolling - thickness of the current collector).

[0134] Specific surface area test method: Use a specific surface area analyzer and calculate the specific surface area of ​​the powder based on the powder gas adsorption and desorption curve. (Disassemble the battery cell to obtain the positive electrode sheet, soak it in NMP to remove the PVDF binder, and after drying, remove the conductive agent by solution centrifugation or calcination in the air to obtain the positive electrode active powder material; disassemble the battery cell to obtain the negative electrode sheet, soak it in deionized water to remove the CMC and SBR binders, and after drying, remove the conductive agent by centrifugation or calcination in the air to obtain the negative electrode active powder material).

[0135] Ionic conductivity test method: Use a conductivity meter to test the electrolyte ion conduction impedance at room temperature 25±5℃, and use the formula σ=L / R*S to calculate the electrolyte ion conductivity, where L is the distance between the electrode plates, S is the electrode plate area, and R is the electrolyte ion conduction impedance.

[0136] Viscosity test method: The viscosity of the electrolyte was tested using a rotational viscometer at room temperature 25±5°C (standard method GB / T2794).

[0137] Dielectric constant test method: Use a dielectric constant tester at room temperature of 25°C to calculate the dielectric constant by measuring the capacitance value in the medium and the capacitance value in vacuum.

[0138] It can be understood that the types of the various lithium-ion batteries in the embodiments of the present application include but are not limited to soft-pack cells, cylindrical cells and square-shell cells, and the sizes are not specifically limited. The cells can be further assembled into product forms such as energy storage systems / power battery packs.

[0139] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator between the positive electrode sheet and the negative electrode sheet, and an electrolyte that soaks the separator; wherein the lithium-ion battery satisfies at least one of the following conditions: (1) The positive electrode sheet comprises a positive electrode current collector and a positive electrode material layer coated on both sides of the positive electrode current collector. The positive electrode material layer comprises a positive electrode active material. The surface density of the positive electrode material layer is Wc, in g / cm 2 The specific surface area of ​​the positive electrode active material is Sc, in m 2 / g; the particle size distribution of the positive electrode active material is Lc, and the particle size distribution Lc of the positive electrode active material is Lc=(D90c-D10c) / D50c; Kc=Lc×Wc / Sc, and the value of Kc satisfies 3.00≤Kc≤6.50; D90c / D50c / D10c represent the particle sizes corresponding to the cumulative particle size distribution percentages of the positive electrode active material particles reaching 90% / 50% / 10% respectively; (2) The negative electrode sheet includes a negative electrode current collector and a negative electrode material layer coated on both sides of the negative electrode current collector. The negative electrode material layer includes a negative electrode active material. The compaction density of the negative electrode material layer is Pa, in units of g / cm 3 The specific surface area of ​​the negative electrode active material is Sa, in m 2 / g; the particle size distribution of the negative electrode active material is La, and the particle size distribution La of the negative electrode active material is La=(D90a-D10a) / D50a; Ka=La×Pa / Sa, and the value of Ka satisfies 0.50≤Ka≤1.50; D90a / D50a / D10a represent the particle sizes corresponding to the cumulative particle size distribution percentages of the negative electrode active material particles reaching 90% / 50% / 10% respectively; (3) The ionic conductivity of the electrolyte is σ e , unit S / cm; viscosity is recorded as η e , unit is mPa / s; dielectric constant is ε e , Ke=σ e ×ε e / η e , the value of Ke satisfies 0.285≤Ke≤0.400; wherein, the test temperature of the ionic conductivity and viscosity is room temperature 25±5°C.

2. The lithium-ion battery according to claim 1, characterized in that The lithium-ion battery at least satisfies condition (1).

3. The lithium-ion battery according to claim 2, characterized in that: The lithium ion battery satisfies at least conditions (1) and (2).

4. The lithium-ion battery according to claim 3, characterized in that: The lithium ion battery satisfies conditions (1) to (3) simultaneously.

5. The lithium ion battery according to any one of claims 1 to 4, characterized in that: The specific surface area Sc of the positive electrode active material is 5 to 20 m 2 / g, the particle size distribution of the positive electrode active material is Lc is 1.0-4.0, and the compaction density of the positive electrode material layer is 2.20-2.80 g / cm 3 , surface density is 15~65mg / cm 2 .

6. The lithium ion battery according to any one of claims 1 to 5, characterized in that: The positive electrode active particles include at least one of lithium iron phosphate particles, surface-coated lithium iron phosphate, or doped and modified lithium iron phosphate.

7. The lithium ion battery according to any one of claims 1 to 6, characterized in that: The negative electrode active material comprises at least one of graphite, surface-coated graphite, surface chemically modified graphite or element-doped graphite; The specific surface area Sa of the negative electrode active material is 0.5 to 3 m 2 / g, and the particle size distribution of the negative electrode active material is La of 1.0 to 2.

0.

8. The lithium ion battery according to any one of claims 1 to 7, characterized in that: The compaction density of the negative electrode material layer is 1.20 to 1.80 g / cm 3 , surface density is 10~40mg / cm 2 .

9. The lithium ion battery according to any one of claims 1 to 8, characterized in that: The ionic conductivity σ of the electrolyte e 8.0~14.0*10 -3 S / cm, the viscosity η of the electrolyte e 2.0~4.0mPa / s.

10. An electrical device, characterized in that: Comprising a lithium ion battery as claimed in any one of claims 1 to 9.